Pengaruh Pengolesan Aloe Vera terhadap Proses Perubahan Derajat Luka Dekubitus: The Effect of Aloe Vera Application on the Degree of Pressure Ulcer Healing - Arlis, Arlis; Sarah, Maita; Mutuah, Desika (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Pressure ulcers are a serious health issue commonly found in patients with prolonged bed rest, particularly stroke patients. These wounds pose a risk of infection, increase morbidity and mortality rates, and prolong hospitalization. One natural therapeutic alternative increasingly used is Aloe vera gel, known for its antioxidant, anti-inflammatory properties and ability to accelerate tissue regeneration. The aim of this community service project was to determine the effect of Aloe vera application on changes in the severity of pressure ulcers in hospitalized patients. This study employed a quasi-experimental design with a one-group pretest–posttest approach. The subjects were all stroke patients with pressure ulcers at H. Adam Malik General Hospital, Medan, totaling 20 individuals selected through total sampling. The intervention involved applying Aloe vera gel once daily during the treatment period. The instrument used was an observation sheet for ulcer grading based on standard pressure ulcer scales. Data were analyzed using the paired t-test to assess changes in ulcer severity before and after the intervention. The results showed a significant improvement in pressure ulcer grades after the application of Aloe vera. Prior to the intervention, 15% of patients had grade 4 ulcers; post-intervention, no patients remained in grade 4. Meanwhile, the percentage of patients with grade 3 ulcers increased from 25% to 40%, indicating tissue recovery and wound healing progression. Statistical analysis yielded a p-value of 0.000, indicating a significant effect of Aloe vera application on the severity of pressure ulcers. In conclusion, Aloe vera application has a positive effect on pressure ulcer healing and can be considered a practical and affordable herbal therapy alternative. It is recommended that the wider community, especially families caring for bedridden patients, consider using Aloe vera in the care of mild to moderate wounds, while continuing to consult healthcare professionals.